Islamic Ethics and Values in the Shopee Affiliate Program: Qawaid Fiqhiyyah Approach - Isnania Wiaam; Khoirun Nisa'; Sinta Thia Anggraeni (Demak Universal Journal of Islam and Sharia, 2024)
This research aims to review the application of ethics and Islamic values in the Shopee Affiliate program with the Qawaid Fiqhiyyah approach. This study uses a qualitative analysis method. There are two types of data collected, namely primary data and secondary data. Primary data includes participatory observation of how the Shopee Affiliate program is run and interactions between platforms, affiliates, and consumers in the context of Islamic ethics. Secondary data includes journal articles, books, case reports in Islamic law journals, and fiqh books. The data was analyzed using the document analysis method to produce relevant findings regarding the application of Qawaid Fiqhiyyah in the Shopee Affiliate program, with a focus on ethical aspects and compliance with Sharia principles. The results show that the Shopee Affiliate program generally supports ethical principles and Islamic values, but there is room for improvement in aspects of transparency, fairness, and social responsibility. The study provides recommendations for improving affiliate business practices to be more aligned with Islamic ethical principles and has the potential to serve as a model for other e-commerce platforms in conducting ethical and responsible business.